Incorporation and solidification mechanism of manganese doped cement clinker - Yang, Nan; Li, Aihong; Liu, Qing; Cui, Yanshuai; Wang, Zhaojia; Gao, Yukun; Guo, Jianping (Frontiers in Chemistry, 2023)
Using municipal and industrial solid waste as substituted raw material and fuels in cement rotary kiln co-processing is considered as an economic and environment friendly proposal. However, heavy metal in solid waste is becoming a growing concern in the field of cement rotary kiln co-processing technique. As the solidification mechanism of heavy metals in cement clinker is directly related to stabilization, it is a key issue worth exploring. Cement clinkers doped with MnO2 (0.0-5.0% wt.%) were prepared in laboratory to investigate the impacts of extrinsic Mn to the cement clinker calcination. X-ray diffractometer patterns performed insignificant change due to the fixed Mn have little influence to the mineral lattice structure. Raman spectra and X-ray photoelectron spectroscopy revealed the transformation of silicate phase while the dosage of Mn increased. Moreover, the satisfied solidification ration promised the incorporation effect of Mn in cement clinkers. These results offered evidence to the influence rule of Mn in cement clinker calcination process. Furthermore, the Raman technology is expected to exhibit great potential for qualitative and semi-quantitative analysis of cement rotary kiln co-processing cementitious materials, which can promote the progress of cement green manufacturing technology.